Physical Environment of High School Technology Laboratories Move Toward Flexible Approaches - Bùi , Văn Hồng (Journal of Technical Education Science, 2010)
The versatile high school technology laboratories are where the teaching activities for both theory and practice take place. The physical environmental factors are built according to Vietnam standards, consistent with the characteristics of each subject and served for whole class teaching, group teaching as well as individual work.